Sistema de controle fuzzy na operação otimizada de redes setorizadas com bombeamento direto - Mendonça, Kamilla Pimentel (2016)
To ensure the supply of the population with the conscious use of hydraulic and electrical resources. This is the present challenge of managers and water supply companies. In a society increasingly aware and concerned about the increase of unbridled consumption, the possibility of efficient use of indispensable resources for human development comes as an incentive to fostering new technologies and research. This paper proposes the use of fuzzy logic as robust control system, which was applied on a test rig that simulates the supply of a network with two different topographical pressure zones. Controllers are important tools in the operation of automated processes aimed at carrying out an operation, in order to make the most of the tools and equipment that make up a system. In this research, we developed two controllers, one applicable in a decentralized system and the other to a centralized system. The controller objective is to ensure the operating pressures in two topographical zones through the control of the drive system‟s frequency, formed by a motor pump assembly; and through the angulation of a pressure reducing valve located before the lower zone. The reported results were promising since, for the two different systems, the controller could perform, taking the pressure at their reference values, reducing the energy consumption when compared to a system with no controller.